Treatment of e-cigarette use among hospitalised adolescents and young adults: a protocol for intervention development and evaluation of preliminary efficacy and implementation outcomes in a randomised controlled trial - Delwyn Catley; Kimber P Richter; Karen Wilson; Shelbie Wooten; Melissa K Miller; Abbey Masonbrink (BMJ Open)
Introduction Hospitalisation represents an opportunity to identify and treat e-cigarette use among adolescents and young adults (AYAs). Knowledge on how to provide this care is lacking. We aim to fill this gap by developing an e-cigarette use intervention and evaluating preliminary efficacy and implementation outcomes among hospitalised AYAs.Methods and analysis We will enrol 144 hospitalised AYAs (14–21 years) who report past 30-day e-cigarette use and randomise 2:1 to intervention or control arms. We will develop an evidence-based intervention that includes education, motivational interviewing, quit planning and nicotine replacement therapy prescription offered confidentially in person during the hospital stay and 4 weekly phone booster sessions. Control participants will receive brief advice and quit programme resources. We will assess self-reported demographics, e-cigarette use behaviours, nicotine dependence, motivation and confidence to quit at baseline and postintervention. Our primary outcome is self-reported 30-day point prevalence e-cigarette abstinence at the 3-month follow-up with biochemical salivary cotinine confirmation. Our secondary implementation outcomes are feasibility, acceptability and fidelity. We will assess our primary outcome using a generalised linear model assuming an underlying binomial distribution and logit link function. X2 (categorical variables) and Wilcoxon rank-sum (continuous variables) tests will be used to assess differences between groups.Ethics and dissemination Careful consideration will be given to ethical recruitment and implementation of all elements of the study. Our study protocol and documents will be reviewed and approved by the institutional review board at the affiliated academic institution. Only approved study team members will access participant data, and all data will be managed in accordance with institutional review board and Health Insurance Portability and Accountability Act (HIPAA) requirements. Study results will be disseminated to our public committee, youth research advisory board, to relevant stakeholders and through publication.Trial registration number NCT05936099; registered on 30 June 2023. Study recruitment and enrolment began in August 2023 and is ongoing.